A política distributiva da coalizão - Fernando Meireles (2019)
This thesis investigates whether in fl uential parties in the ministries' investments in coalition presidentialism. In doing so, it diverges from the current view in distributive policy studies that presidents centralize the allocative decisions of their governments. My argument is that by offering ministries to other parties in exchange for legislative support, presidents share the government's distributive policy with its coalition partners. As a result, parties gain in fl uence and expertise on the investments of the committees they lead and, consequently, the means to bring more resources to their constituencies. Document this party electoral connection with data from more than twenty years of discretionary transfers from ministries to prefectures in Brazil, information obtained from fieldwork and a series of natural experiments. My results show that municipalities command and receive more resources from ministries led by the parties of their mayors, and in turn they mobilize votes for their legends in the general elections. Among other contributions, the thesis offers causal evidence that parties derive particularistic benefits from the occupation of ministries; shows that this creates inequalities in the provision of public goods in the country; and documents how the Brazilian parties, considered weak by many analysts, articulate the supply and demand for public resources strategically to win votes and gain influence in national politics.